Impact of Destination Image, Service Quality, and Location on Visitor Satisfaction through Visitor Decision on Global Waterboom in Pati Central Java - Jessica Manurung, R; ., Wahyono (KnE Social Sciences, 2018)
This research is based on some previous research on Image Imagery, Service Quality, Location and Visitor’s Decision on Visitor Satisfaction. This study is also based on the phenomenon that occurs indicate that the fluctuations that occur in the number of visitors and revenue from Global Waterboom. This study aims to determine the effect of Destination Image, Service Quality, and Location Against Global Waterboom Visitor Satisfaction in Pati Central Java. The variable of visitor decision is used as intervening variable in this research. Population in this research is visitor of Global Waterboom in Pati Central Java. The sample in this study amounted to 116 respondents Data collection methods used were the method of questionnaires, observation, interviews, and literature study. Data analysis using path analysis, whereas research includes Destination Image, Service Quality, Location, Visitor Satisfaction, Visitor Decision. The result of the research shows that Citra Destination has an effect on visitor satisfaction either directly or indirectly through visitor decision. Location affects visitor satisfaction through visitor decisions. Service Quality does not give a direct influence to visitor satisfaction with significance level > 0.05. Locations do not directly influence visitor satisfaction with significance levels> 0.05. This study proved that the influence of Image Imagery, Service Quality and Location to Visitor Satisfaction is equal to 53.6%. Conclusion from the research that the quality of service that has the least influence on the satisfaction of visitors either directly or through the decision of the visitor. The advice given by the manager of Global Waterboom is the need to add the number of officers as well as to train the officers, so that the officers can provide excellent service, need improvement of facilities and appearance of the building, and traffic arrangement so as not to jam when entering the area. For further researchers to examine more than one waterboom attraction in Pati and consider other variables. Keywords: Image of The Destination, Quality of Service, Location, Satisfaction of Visitors, Visitor’s Decision.